Aanalyzing risks of incidence of tick-borne encephalitis in areas with different climatic and geographical conditions - N.K. Tokarevich; A.A. Tronin; R.V. Buzinov; O.V. Sokolova; T.N. Unguryanu (Analiz Riska Zdorovʹû, 2021)
Ticks are natural reservoirs and vectors of a virus that is an infectious agent of tick-borne encephalitis, a communicable disease with great medical and social significance. Tick-borne encephalitis (TBE) is widely spread in Arkhangelsk region (AR) located in the Arctic zone in Russia where substantial climatic changes are taking place at the moment.